2002
DOI: 10.17221/10312-pps
|View full text |Cite
|
Sign up to set email alerts
|

Development of RT-PCR tests for the routine detection of latent and ILAR viruses in fruit trees

Abstract: The detection throughout the year of latent and ILAR viruses in fruit trees by classical serological tests appears to be unreliable. Recently, these problems have smoothed themselves out by the use of molecular methods. We have developed RT-PCR protocols which are simple and reliable for routine detection of these viruses throughout the year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The position of a mismatch is crucial to the specificity of an MGB probe. MGB probes have been successfully employed to detect single‐nucleotide mutations in the central region (Marbot et al , 2002; Salmon et al , 2002 b ) or the 3′ terminal region (Kutyavin et al , 2000; Salmon et al , 2002 a ; Massart et al , 2005) of the probe. Yao et al (2006) observed that two mismatches in the centre of the probe‐annealing region generated a signal in their MGB probe assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The position of a mismatch is crucial to the specificity of an MGB probe. MGB probes have been successfully employed to detect single‐nucleotide mutations in the central region (Marbot et al , 2002; Salmon et al , 2002 b ) or the 3′ terminal region (Kutyavin et al , 2000; Salmon et al , 2002 a ; Massart et al , 2005) of the probe. Yao et al (2006) observed that two mismatches in the centre of the probe‐annealing region generated a signal in their MGB probe assay.…”
Section: Discussionmentioning
confidence: 99%
“…TaqMan MGB probes display higher specificity than classical TaqMan probes (Yao et al , 2006). Successful discrimination of a single mismatch has been achieved by various authors (Marbot et al , 2002; Salmon et al , 2002 a ; Yoshitomi et al , 2003; Van Hoeyveld et al , 2004; Massart et al , 2005). Yet, recent studies (Yao et al , 2006) have shown that a TaqMan MGB probe may tolerate one or two mismatches with its template and cause a nonspecific fluorescence emission.…”
Section: Introductionmentioning
confidence: 99%
“…The DNA extraction efficiency of this crude preparation method was further assessed by semi-quantitative evaluation of phytoplasma DNA using real-time PCR. The application of crude preparation of infected plants has been previously tested for virus detection by PCR amplification (Marinho et al, 1998;Marbot et al, 2002;Delanoy et al, 2003); furthermore a simple plant tissue preparation without homogenization suitable for detection of viruses by PCR was described by Thomson and Dietzgen (1995).…”
Section: Introductionmentioning
confidence: 99%